PTU-188 "Knitted" oesophageal stents: superior conformability with no trade off. (28th May 2012) - Cain, J R; Westwood, T; Gordon, C; Frost, R A; Laasch, H-U
Abstract : Introduction: Knitted enteral stents have reduced stent shortening and no axial straightening forces, resulting in better conformability to tortuous anatomy compared to conventional braided stents. The first covered removable oesophageal stent is now available consisting of a knitted Nitinol skeleton with large heads covered in silicone, but the shaft only externally covered by an ePTFE membrane. In vitro it has better conformability but comparable radial force to standard braided stents. We report the first experience world-wide with this type of device. Methods: All consecutive patients over a 9-month period referred for oesophageal stenting had an Egis stent (BVM Medical, Hinckley, UK/S&G Biotech, Seoul, Korea) placed under fluoroscopic guidance. Stents with anti-reflux valve were used if the lower end had to be placed in the stomach. Patients were followed up prospectively until death or stent failure. Clinical outcome was compared to the results from the national Registry of Oesophageal Stenting (ROST). The device is CE marked and was used within its license. Institutional review board was nevertheless sought and granted. The manufacturer made 30 stents were available for evaluation free of charge. Results: 22 patients with malignant dysphagia and 2 with a benign post-radiation stricture had an EGIS oesophageal stent inserted. Median immediate stent expansion at insertion was 45% (25%–100%) increasing to 100% (60%–100%) after 1 week. Minor complications occurred in 8% compared to 14% in the national audit. No stent migrated from the oesophagus above the cardia, partial migration occurred in 1/15 stents (9.8%) placed across the GO-junction, comparing favourably to a migration rate of 4.3% (mid-oesophagus) and 18% (cardia) from the national audit. Improvement in dysphagia was comparable with a pre-stent median score of 3 (2–4) improving to 2 (0–3) at 48 h and to 1 (1–3) after 1 week. The two stents inserted for benign strictures were removed endoscopically by inversion through capture of the lower purse string. Initial difficulties with the delivery system were identified and corrected by the manufacturer. Conclusion: Limited first experience shows the EGIS oesophageal stent to perform at least as good as the large variety of existing oesophageal stents. There may be a benefit in terms of reduced stent migration, particularly if placed across the adverse anatomy of the GO-junction, but more extensive experience is required. Palliation of dysphagia is as good as with conventional stents. The stent should be particularly considered in tortuous anatomy due to the excellent conformability. Competing interests: J Cain: None declared, T Westwood: None declared, C Gordon: None declared, R Frost: None declared, H-U Laasch Consultant for: S&G Biotech. Reference: 1. British Society of Interventional Radiology (BSIR) . ROST - Registry of Oesophageal Stenting, First Report 2004 . Henley-on-Thames: Dendrite Clinical Systems, 2004.